ASPEK PENTING DISPOSISI DALAM PEMBERDAYAAN MASYARAKAT DI PERKOTAAN - Ipah Ema Jumiati (Universitas Sultan Ageng Tirtayasa, 2014)
Urban poverty emerged as an important issue, which needs to be resolved in order to be removed. The structural dimensions of poverty arises because the city offers a lot of hope has been much in demand by people who want a fringe and rural life better. Therefore, through the implementation of the National Program for Community Empowerment ( PNPM) by taking the expected locus in Serang city poor communities can be empowered with an important role in the disposition factor of institutional PNPM Mandiri, the basis of the theory of Edward III (1980 ). Through this article, can be described that the presence of the implementing agency and has a major role in determining the success of policy implementation. It can be seen by looking at how the appointment of field officers involved in the implementation of the National Program for Community Empowerment ( PNPM), then whether they have sufficient skills and experience in carrying out its duties, as well as how the incentives provided for this in accordance with the severity of what works in implementation of PNPM Mandiri or not. The results of the research found that the appointment of field officers involved in PNPM Mandiri has not fully have the skills and experience to implement the program. This condition leads to lower people's understanding of the purpose of each activity and the implementation of PNPM Mandiri .